Aestheticism and Deconstruction : Pater, Derrida, and de Man. - Loesberg, Jonathan (Princeton legacy library., 2014)
Considered an exemplar of ""Art-for-Art's Sake"" in Victorian art and literature, Walter Pater (1839-1894) was co-opted as a standard bearer for the cult of hedonism by Oscar Wilde, and this version of aestheticism has since been used to attack deconstruction. Here Jonathan Loesberg boldly uses Pater's important work on society and culture, Studies in the History of the Renaissance (1873), to argue that the habitual dismissal of deconstruction as ""aestheticist"" fails to recognize the genuine philosophic point and political engagement within aestheticism. Reading Jacques Derrida and Paul d